(untitled) (Analytic Teaching, 1982)
Introduction: It would be impossible to count the times adults have demanded of children, "Why did you do that? Don’t you ever think before you do something!" We expect children to reach conclusions that are acceptable to adults, but seldom do we realize that we don’t adequately prepare children for that thinking process. All too often we pump facts into children and require them to spout back the same material. When we ask questions that require reasoning to answer, and the child answers incorrectly, we say that the child isn’t capable of reasoning.